2014
DOI: 10.1507/endocrj.ej13-0398
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of <i>ABCC8</i>, <i>KCNJ11</i>, <i>GLUD1</i>, <i>HNF4A</i> and <i>GCK</i> genes in 30 Chinese patients with congenital hyperinsulinism

Abstract: We conducted a cohort study to elucidate the molecular spectrum of congenital hyperinsulinism (CHI) in Chinese pediatric patients. Thirty Chinese children with CHI were chosen as research subjects, 16 of whom were responsive to diazoxide and 13 of whom were not (1 patient was not given the drug for medical reasons). All exons of the adenosine triphosphate (ATP)-sensitive potassium channel (KATP channel) genes KCNJ11 and ABCC8, the hepatocyte nuclear factor 4 α (HNF4A) gene, and the Glucokinase (GCK) gene as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
13
0
1
Order By: Relevance
“…A total of 207 cases, 1 case from our own department together with the 206 cases of CHI reported previously from China ( 11 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ) were available for analysis. Among them, 154 cases were from Beijing city, 32 from Shanghai city, 14 from Guangdong province, 4 from Zhejiang province, and 1 case each from Hunan, Sichuan, and Shandong provinces.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 207 cases, 1 case from our own department together with the 206 cases of CHI reported previously from China ( 11 , 12 , 13 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ) were available for analysis. Among them, 154 cases were from Beijing city, 32 from Shanghai city, 14 from Guangdong province, 4 from Zhejiang province, and 1 case each from Hunan, Sichuan, and Shandong provinces.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to diagnose and treat these infants with CHI at the earliest to alleviate the degree of brain damage. Several studies ( 10 , 11 , 12 , 13 ) have already summarized the clinical and genetic characteristics of CHI in Beijing and Shanghai; however, studies throughout China are yet lacking. In this article, we aimed to review the present knowledge on the clinical presentation, therapeutic outcomes, and genetic mutations of CHI in the Chinese population and to compare this knowledge with that in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we reported the clinical characteristics, laboratory data and genetic features of 65 patients with CHI, which was the largest CHI cohort in southern China. Until now, there have been no nationwide data regarding this disorder in China, although several studies have summarized the clinical and genetic characteristics of CHI in northern and eastern China (20,21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, nine Chinese GDH-HI patients have been reported in four different studies [ 5 8 ]. However, little is known about clinical characteristics, long-term follow-up results, and molecular spectrum of Chinese patients [ 5 , 6 , 8 , 9 ]. In this study, we report 26 cases of GDH-HI that were confirmed by genetic diagnosis.…”
Section: Introductionmentioning
confidence: 99%